Understanding the degradation mechanisms of Ba-based double perovskite electrodes for solid oxide electrochemical cells - Lee, Jinsil; Kim, Taeyun; Lee, Hyeon Jin; Yoon, Kyung Joong; Lee, Jong-Ho; Joo, Jong Hoon (Elsevier BV, 2025)
To shed light on the degradation mechanisms, this study investigated the electrochemical characteristics and phase stability of PrBaFe2O5+omega (PBF) a representative double perovskite material, under atmospheric conditions. A ceramic manufacturing process was applied to fabricate dense bulk electrode for analyzing the surface exchange reaction comprehensively. Furthermore, a defect concentration analysis was performed, which offered insights into the double perovskite material properties and affirmed the accuracy of the analysis system by comparing the surface exchange coefficients utilizing the fabricated dense bulk electrode. When surface exchange reactions were measured in an atmosphere containing CO2 and moisture, significant degradation was observed. Our findings indicated that the deterioration in surface exchange reactions of the double perovskite electrode was primarily due to the hydroxide formation in the atmosphere, leading to phase decomposition.